Effectiveness of chronic hepatitis C treatment with direct-acting antivirals in the Public Health System in Brazil - Holzmann,Iandra (2018)
ABSTRACT Introduction Chronic hepatitis C virus infection is one of the major causes of cirrhosis, hepatocellular carcinoma and liver transplantation. Treatment using direct-acting antivirals has revolutionized the treatment of hepatitis C virus, increasing long-term prognosis after cure. The goal of the present study was to evaluate the effectiveness of direct-acting antivirals in a Public Health System in southern Brazil. Methods A retrospective study evaluated all patients with chronic hepatitis C virus infection who underwent treatment at one center of the Public Health Department of the State of Rio Grande do Sul - Brazil, according to the Brazilian Clinical Protocol and Therapeutic Guidelines. The effectiveness was assessed in terms sustained virological response 12 weeks after the end of treatment. Results A total of 1002 patients who were treated for chronic hepatitis C virus infection were evaluated. The mean age was 58.6 years, 557 patients (55.6%) were male and 550 (54.9%) were cirrhotic. Overall sustained virological response was observed in 936 (93.4%) patients. There was a difference in sustained virological response rate varied according to sex, 91.6% in men and 95.7% in women (p= 0.009), length of treatment in genotype 1, 92.7% with 12 weeks and 99.1 with 24 weeks (p= 0.040), and genotype, 94.7% in genotype 1, 91.7% in genotype 2, and 91.4% in genotype 3 (p= 0.047). Conclusion The treatment of chronic hepatitis C virus infection for genotypes 1, 2 or 3 with the therapeutic regimens established by the Brazilian guidelines showed high rates of SVR, even in cirrhotic patients.